The association of mode of location activity and mobility with acute coronary syndrome: a nationwide ecological study. (29th January 2021) - Mohammad, M. A.; Koul, S.; Gale, C. P.; Alfredsson, J.; James, S.; Fröbert, O.; Omerovic, E.; Erlinge, D.
Abstract: Background: We aimed to study the effect of social containment mandates on ACS presentation during COVID‐19 pandemic using location activity and mobility data from mobile phone map services. Methods: We conducted a cross‐sectional study using data from the Swedish Coronary Angiography and Angioplasty Registry (SCAAR) including all ACS presentations during the pandemic until 7 May 2020. Using a count regression model, we adjusted for day of the week, daily weather and incidence of COVID‐19. Results: A 10% increase in activity around areas of residence was associated with 38% lower rates of ACS hospitalizations, whereas increased activity relating to retail and recreation, grocery stores and pharmacies, workplaces and mode of mobility was associated with 10‐20% higher rates of ACS hospitalizations. Conclusion: Government policy regarding social containment mandates has important public health implications for medical emergencies such as ACS and may explain the decline in ACS presentations observed during COVID‐19 pandemic. Abstract :